Social responsibility in nongovernmental organizations of the health sector in the state of Lara, Venezuela: A study from the paradigm of sustainable human development (Mayéutica Revista Científica de Humanidades y Artes, 2023)
The purpose of the research was to analyze, based on the versions of its executives, the Social Responsibility management processes of three NonGovernmental Organizations ofthe health sector of the estado Lara, Ascardio Alaplaf and the Cruz Roja, from the Sustainable Human Development approach. It is a qualitative research with interpretativeparadigmatic posture with a phenomenologicalhermeneutical approach. The technique of gathering information was the indepth interview, and the data was interpreted from thehermeneutics of the managers' versions. For the analysis of the information, theoretical triangulation was made of the information obtained, the categories and the informants'versions. Among the findings, it is highlighted that Social Responsibility in NGOs is conceived, even without explicitly establishing it in its management philosophy, as a commitment with workers, the community, users and society in general, in line with the economic dimensions, Social and Environmental Development of Sustainable Human Development and the Sustainable Development Goals of the United Nations. In addition, the NGOs in their more than four decades of operation have managed to sustain themselves financially even in the times of humanitarian emergency that Venezuela is going through.
Keywords: Social Responsibility; NonGovernmental Organizations; Sustainable Human Development; Sustainable Development Goals